2021
DOI: 10.3390/agronomy11061059
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Total Phenols, Tannins, Anthocyanins Content in Myrtus communis L. and Antioxidant Activity Evaluation in Function of Plant Development Stages and Altitude of Origin Site

Abstract: Most of the biological properties of myrtle (Myrtus communis L.) are linked to the antioxidant activity of the phenolic compounds present in the extracts. In this study, the content of total phenols, tannins, and anthocyanins of acidified ethanol extracts of berries and leaves of five myrtle cultivars was quantified during the whole fruit development. In some development stages, the antioxidant activity (AA) of both tissues was evaluated with FRAP, ABTS, DPPH, β-carotene assays, and spectroscopic method (EPR).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 66 publications
(87 reference statements)
1
9
4
Order By: Relevance
“…The proportion of anthocyanins can reach 56% of total phenols in some berries. Anthocyanins are thought to play a minor role in the antioxidant activity of berries . Our studies confirmed the statement of other authors ,, that antioxidant activity depends on the concentration of phenolics and ascorbic acid, but not on the content of anthocyanins.…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of anthocyanins can reach 56% of total phenols in some berries. Anthocyanins are thought to play a minor role in the antioxidant activity of berries . Our studies confirmed the statement of other authors ,, that antioxidant activity depends on the concentration of phenolics and ascorbic acid, but not on the content of anthocyanins.…”
Section: Discussionsupporting
confidence: 92%
“…A correlation between the tested antioxidant assays with TFC were positively high (0.995 < r < 1.000), indicating that T. musilii methanolic extract possesses comparable activities in all four assays. In fact, it has been well documented that TPC, TFC, and TTC found in the plant kingdom are responsible for their antioxidant activities due to their redox properties [ 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true since the composition of extracts can vary drastically depending on the plant location [22], time of year [23,24], the stage of the plant (young plant, plant at the time of flowering etc.) [25][26][27] and the plant part that is extracted [28,29]. Previous studies have also shown that the phenol content in the trunk drastically varies with respect to height [30], and between sapwood, heartwood, knotwood and branchwood [31].…”
Section: Introductionmentioning
confidence: 99%